Epigenetic boundaries of tumour suppressor gene promoters: the CTCF connection and its role in carcinogenesis - Recillas-Targa, Felix (John Wiley & Sons, Ltd, 2006)
Genetic and epigenetic regulations are essential mechanisms that ensure proper early and subsequent mammalian programming of diverse cellular processes. These mechanisms affect transcriptional regulation, stem cell determination and cell cycle control, including senescence and aging. It is not surprising that perturbation of the exquisite balance between genetic and epigenetic regulation can lead to diverse diseases, including cancer. Histone covalent modifications and DNA methylation do not explain all epigenetic phenomena. We describe a previously unsuspected epigenetic factor and propose the incorporation of the 11-zinc finger CCCTC-binding factor, known as CTCF as a novel and multifunctional epigenetic regulator.